Corporate Social Responsibility as a Tool for Sustainability in Entrepreneurship - Fixen, Megan (American Journal of Management, 2025)
Corporate social responsibility (CSR) is increasingly gaining attention as an essential component of business. In the current environment, entrepreneurs may be searching for strategies to maintain a competitive advantage. CSR-based initiatives may help businesses differentiate themselves from others in the market, attracting customers that align with their values. This paper includes a review of the CSR concept and the role that CSR can play in increasing competitiveness in entrepreneurship. The literature revealed that businesses that engage in CSR based activities see increased customer loyalty, trust, and profit. Therefore, engaging in CSR behaviors may enhance sustainability and growth for entrepreneurial ventures.